Effects of spatial constraint on oxidative stress during individual transport of Larimichthys crocea and its preliminary mitigation - Sunzhaocong Lan; Jiahui Wang; Xiaoqing Lei; Dejun Feng; Fukun Gui; Guangyang Zhang; Xunmeng Li (Aquaculture, 2027)

Numerical investigation of waste collection behavior in octagonal aquaculture tanks of deep-sea aquaculture vessels under multi-degree-of-freedom excitations - Haoran Cheng; Dejun Feng; Yanfei Wu; Lianhui Wu; Jiajun Hu; Fuzhi Zu; Hongzhou Chen; Fukun Gui; Xiaoyu Qu (Ocean Engineering, 2026)

Influence of structural parameters on characteristics of flow field in vessel-shaped aquaculture cages - Hongzhou Chen; Xucheng Jiang; Dejun Feng; Xu Yang; Lili Mei (Ocean Engineering, 2026)

Seismic performance of full-scale modular steel frame: Components and joints - Chao Yang; Lifei Feng; Hao Zhang; Dejun Zhang; Jinping Ou (Engineering Structures, 2026)

Flow Characteristics and Pipeline Stability in Slope-Confined Submarine Canyons - Dejun Wang; Jun Huang; Xianhong Feng; Huaqing Liu; Yuqi Dong; Zhimeng Gong; Zhihui Jiao; Yunfei Teng; Zhichao Shen; Yan Qu (Journal of Marine Science and Engineering, 2026)
Numerical simulations are conducted to investigate the near-bed flow behaviors of submarine canyons with periodic ridge-valley topography on continental slopes. In the numerical simulation, two topographic parameters are defined: α represents the basal slope angle of the continental slope, and β denotes the side slope angle of the submarine canyon. The topographic modulation of these two parameters on near-bed flow velocity and pipeline on-bottom stability is explored. The results show that the ribbed slope exerts two distinct modulation mechanisms on near-bed flow fields, which are governed by the relative angle between incoming flow and ridge-valley structures. When the flow is perpendicular to the canyon axis (θ = 0°), local topographic contraction and expansion accelerate flow over ridge crests and reduce near-bed velocity in valleys as β increases. In contrast, when the flow is parallel to the canyon (θ = 90°), lateral confinement by bilateral ridges forms a topographic channel, leading to persistent flow acceleration throughout the entire valley area. Moreover, such directional velocity differences substantially alter the on-bottom stability of pipelines deployed within the canyon. Two pipe-soil interaction models are employed in the stability analysis: the Verley-Lund model for a flat clayey seabed and the Slope-Silt model for a sloping silty seabed. The sensitivity of their predictions to soil undrained shear strength is further evaluated.

Experimental investigation into the dynamic and mooring response of a novel submersible cage to waves at various depths - Wenjian Wang; Dejun Feng; Can Cui; Meihan Chen; Tianrui Ji; Xu Yang; Hongzhou Chen; Hua Zhang; Jiajun Hu; Lianhui Wu; Fukun Gui; Xiaoyu Qu (Ocean Engineering, 2026)

Optimization of Aeration Tube Configuration Considering the Efficiency of Waste Collection and Water Mixing in Aquaculture Tanks - Can Cui; Dezhen Li; Fuzhi Zu; Dejun Feng; Xiaoyu Qu; Yi Tao (Fishes, 2026)
Proper configuration of aeration tubes is crucial for improving water quality and promoting the welfare and growth of cultured organisms in Recirculating Aquaculture Systems (RASs). To investigate the effects of aeration tube shapes (arc-shaped, disc-shaped, and linear-shaped) and positions (d = r, 1/2r) on performance, this study conducted experiments in a circular RAS tank. Methodologically, feed pellets were used to simulate solid waste, while ink was added to visualize the flow field, and mixing performance was quantitatively assessed using the spatial distribution uniformity. The results indicated that without aeration, the physical presence of the tubes affected waste collection but had minimal impact on water mixing. Under aeration conditions, placing tubes at d = 1/2r instead of d = r resulted in more efficient waste collection and improved water mixing. Waste collection performance was ranked as arc-shaped > disc-shaped > linear-shaped, whereas water mixing performance ranked linear-shaped > arc-shaped > disc-shaped. It is therefore recommended to place arc-shaped aeration tubes at d = 1/2r to achieve optimal overall performance. These findings provide valuable baseline insights into the selection and placement of aeration devices, offering preliminary practical guidance for aquaculture engineering.

Numerical simulation of tidal-driven particulate dispersion and transport in a Larimichthys crocea enclosure aquaculture zone - Guangyang Zhang; Shuaiqing Wang; Yongsen Zhao; Xianyuan Zhou; Dejun Feng; Fukun Gui (Marine Pollution Bulletin, 2026)

Biomass models, allometric relationships, and carbon sink of Sargassum henslowianum in Nan'ao Island - Jing Chen; Jinhuai Ni; Hong Du; Kai Zong; Sunzhaocong Lan; Jianpeng Lu; Dejun Feng; Xu Yang; Guangyang Zhang; Lili Mei; Yuanmin Sun; Xunmeng Li (Regional Studies in Marine Science, 2026)

Assessing the behavior of Larimichthys crocea during the ascent process of the offshore submersible cage - Jinhuai Ni; Sunzhaocong Lan; Yang Gao; Xiaolong Yin; Kai Zong; Jianpeng Lu; Xu Yang; Fukun Gui; Xunmeng Li; Dejun Feng (Aquaculture, 2026)

Corrigendum to “Integration of transcriptomics and metabolomics reveals the effects of sea currents on overwintering of large yellow croaker Larimichthys crocea in cage culture” [Aquaculture, volume 578, 15 January 2024, 740054]. - Huirong Lv; Xiaoyu Qu; Zhangjie Chu; Weiye Li; Xiaolong Yin; Dejun Feng; Jungyeol Park; Junwook Hur; Yang Gao (Aquaculture, 2026)

Comparing the effects of single and coupled sloshing excitation on the self-cleaning hydrodynamic performance of the aquaculture tank on an offshore vessel - Fuzhi Zu; Can Cui; Haoran Cheng; Yanfei Wu; Jiajun Hu; Lianhui Wu; Dezhen Li; Fukun Gui; Dejun Feng; Fei Wang (Ocean Engineering, 2026)

Robust and efficient membrane contactor for carbon dioxide capture enabled by thin-film composite Janus membrane - Wenting Zhou; Chunlei Su; Dejun Feng; Yuanmiaoliang Chen; Liting Pan; Di He; Zhangxin Wang (ENGINEERING Environment, 2026)

Fe-modified CoS2/ZnIn2S4 heterojunction for dual-driven photoactivation of peroxymonosulfate: Efficient degradation of antibiotics in water - Xiao Feng; Qiqi Gan; Zhongliang Li; Yunhong Zhao; Tengfeng Xie; Dejun Wang; Yanhong Lin (Journal of Environmental Chemical Engineering, 2026)

FINDER: Flow-aware intelligent navigation through distilled experience and reinforcement learning for UUVs in complex flow fields - Shuguang Chu; Haihan Feng; Yuheng Ou; Mingwei Lin; Dejun Li (Ocean Engineering, 2026)

Multi-Target Anticoagulant Regulation by Peptides from Medicinal Leeches: A Unique Natural Strategy against Thrombosis - Feng Shi; Qingmei Hu; Yiquan Lin; Sijia Fan; Xueting Cao; Dezhi Yang; Yuanhai Chen; Dejun Kong; Kaiqing Liu; Zichao Liu (Pharmaceutical Research, 2026)

RC-UMT: Multimodal fish feeding intensity classification network with enhanced feature extraction capability in aquaculture - Shantan Li; Xinting Yang; Zhitao Huang; Tingting Fu; Pingchuan Ma; Dejun Feng; Chao Zhou (Aquacultural Engineering, 2026)

Supercritical CO2-assisted pressure homogenization for exfoliating natural graphite toward high-performance graphene cathodes in aluminum-ion batteries - Yue Wu; Jianmin Feng; Li Wang; Jiacheng Qiu; Xuan Song; Xuwang Fu; Ziqi Luo; Jiahan Ma; Xiaoyu Yu; Lei Dong; Yan Han; Conglai Long; et al. (Chemical Engineering Journal, 2025)

Deep learning-based species identification of gymnosperm xylem: The practice in digital forestry - Chang Zheng; Tuo He; Lichao Jiao; Yang Lu; Shoujia Liu; Tianxiao Li; Yuanyuan Miao; Dejun Feng; Jian Lin; Xian Feng; Zhonghua Huang; Min Yu; et al. (Computers and Electronics in Agriculture, 2025)

Morphological feature assessment of Larimichthys crocea for quality grading: a computer vision approach - Dejun Feng; Hang Liu; Lianhui Wu; Xiaoguo Ying; Xiaoyu Qu; Yang Gao; Fukun Gui; Chao Zhou (Aquaculture International, 2025)

Teaching in adverse scenes: a statistically feedback-driven threshold and mask adjustment teacher-student framework for object detection in UAV images under adverse scenes - Hongyu Chen; Jiping Liu; Yong Wang; Jun Zhu; Dejun Feng; Yakun Xie (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Precise catalytic conversion of complex hydrocarbon molecules via “Molecular Scissors” - Shunnian Xu; Kuo Tang; Dejun Shi; Zhiguo Sun; Xiao Feng; Hongxu Gong; Gang Wang (Fuel, 2025)

Dynamic motion response of a large-scale steel aquaculture cage during towing - Shuai Niu; Zhi Wang; Lianyi Guo; Lianghao Tang; Tianyu Gu; Can Cui; Dejun Feng; Fukun Gui; Xu Yang (Frontiers in Marine Science, 2025)
As global aquaculture ventures further into offshore environments, the safe transport of large-scale aquaculture net cages across varied marine conditions has become a critical technical concern. This study conducts a detailed numerical simulation of the wet towing process for an octagonal aquaculture cage using AQWA software, systematically examining the effects of towline length, towing speed, towing configuration, and environmental factors on the cage’s dynamic response and towline load characteristics. The findings reveal that towline length and towing speed are pivotal in determining the pitch amplitude of the cage and the resulting towline tension. Compared to a towline length of 200 m, using a towline length of 150 m combined with a towing speed of 0.5 m/s reduces pitch amplitude by 51.6% and towline tension by 24.8%. Additionally, an interval towing arrangement significantly enhances cage stability while minimizing towline stress. Under conditions of low wave height and longer wave period, the cage’s motion response remains stable, contributing to enhanced transport safety. This research offers critical theoretical foundations and optimization strategies for the wet towing design considerations of offshore aquaculture cages, providing valuable insights to advance transport safety in challenging marine environments.

Contrasting roles of abundant and rare root-associated fungi in wheat: Community assembly, heritability and agronomic impacts - Xia Kang; Yuyin Zheng; Zhihan Feng; Minjie Yao; Xiangzhen Li; Dejun Han; Qingdong Zeng; Hao Tan; Yumin Yang; Jiabao Li (Applied Soil Ecology, 2025)

Study on the Flow Characteristics in a Large Land-Based Circular Aquaculture Tank Based on Field Experiments - Yanfei Wu; Jianeng Chen; Chengxia Jia; Fukun Gui; Qixian Zhou; Dejun Feng; Qingjing Zhang (Journal of Marine Science and Engineering, 2025)
The rapid expansion of large-scale aquaculture has created a demand for more efficient and sustainable farming systems. Among these, land-based circular tank aquaculture is emerging as a key solution due to its high efficiency, scalability, and effective waste management capabilities. Optimizing the hydrodynamic characteristics of these tanks is crucial for improving water quality management and ensuring the health of cultured fish. This study investigates the hydrodynamic characteristics of large land-based circular tanks, focusing on the effects of water pusher configurations and the presence of fish on flow dynamics and sewage collection efficiency. Field experiments were conducted under two conditions: with and without fish, while varying the pusher diameter, deployment angles, and the number of pushers. The flow characteristics at different layers of the tanks were measured using Acoustic Doppler Velocimetry. The results indicate that the pusher deployment has a more significant impact on the flow field and hydrodynamic characteristics compared with the pusher diameter. The optimal configuration for water circulation and sewage collection was identified when the pusher diameter was 11 cm, the deployment angle was 45°, and the number of pushers was 6. The presence of fish significantly influenced the flow field distribution by expanding high velocity flow zones. The findings provide a theoretical basis for optimizing water pusher deployment in large-scale circular tanks with fish, thereby contributing to improved water quality management and fish health.

Laboratory Investigation of the Uplift Resistance of a New Winged H-Pile Anchor Developed for Offshore Marine Aquaculture - Xu Yang; Lianghao Tang; Lili Mei; Tianyuan Zhang; Shuai Niu; Zhefei Sun; Zhenliang Wang; Dejun Feng; Fukun Gui (Journal of Marine Science and Engineering, 2025)
To enhance the stability and safety of marine aquaculture facilities by addressing the limited uplift resistance capacity and susceptibility to deflection of conventional straight-shafted piles, this study introduces an improved H-pile anchor and conducted laboratory experiments. The new anchor incorporates resized H-piles with wing plates added to both sides, optimized for area and placement, as well as an adjusted loading angle. The findings demonstrate a positive correlation between the uplift resistance capacity of the H-pile anchor and its length and width, indicating that while increased pile length significantly enhances resistance, widening has a minimal impact. Additionally, enlarging the wing plate area improves the resistance; however, efficiency (δ) decreases with the increase in the area, suggesting the existence of an optimal size. The optimal wing plate dimensions (L = 80 mm, W = 25 mm) improve uplift resistance by at least 10.6% compared to non-wing pile anchors. Furthermore, positioning the wing plates at the base of the pile anchor rather than the top enhances resistance by approximately 13.8%. Setting the anchor layout angle to 45° reduced the displacement under inclined loads. This research provides essential theoretical support and practical guidance for strengthening the safety and stability of marine aquaculture facilities.

Impact of stocking density of largemouth bass on the self-cleaning performance of a circular aquaculture tank - Xiaoyu Qu; Yi Tao; Dezhen Li; Fuzhi Zu; Yanfei Wu; Fei Wang; Lianhui Wu; Jiajun Hu; Yang Gao; Dejun Feng (Aquaculture, 2025)

Field study on the dynamic characteristics of sewage collection in a circular aquaculture tank - Yanfei Wu; Fukun Gui; Jianxin Yang; Hongfang Qi; Hong Zhang; Yang Wang; Dejun Feng; Qingjing Zhang (Aquaculture International, 2025)

Insight into metabolomics analysis of large yellow croaker liver (Larimichthys crocea) during packaging bag transport - Haofeng Sun; Fukun Gui; Dejun Feng; Ping Wang; Xiaoyu Qu; Shuai Niu; Guangyang Zhang (Aquaculture International, 2025)

DF-DETR: Dead fish-detection transformer in recirculating aquaculture system - Tingting FU; Dejun Feng; Pingchuan Ma; Weichen Hu; Xinting Yang; Shantan Li; Chao Zhou (Aquaculture International, 2025)

Sloshing-induced evolution of self-cleaning performance and flow characteristics within a tank installed on an offshore aquaculture vessel - Dezhen Li; Yi Tao; Fuzhi Zu; Yanfei Wu; Fukun Gui; Yang Gao; Fei Wang; Lianhui Wu; Dejun Feng; Xiaoyu Qu (Ocean Engineering, 2024)

Effect of wing plate structure on uplift resistance capacity of marine aquaculture anchor piles - Fukun Gui; Tianyuan Zhang; Xiaoyu Qu; Xu Yang; Fuxiang Hu; Dejun Feng (Marine Georesources & Geotechnology, 2024)

New insights into interaction between oil and solid during hydrothermal treatment of oily sludge - Qi Li; Dejun Sun; Feng Chen; Haoran Xu; Zhenghe Xu (Journal of Hazardous Materials, 2024)

Integration of transcriptomics and metabolomics reveals the effects of sea currents on overwintering of large yellow croaker Larimichthys crocea in cage culture - Huirong Lv; Xiaoyu Qu; Zhangjie Chu; Weiye Li; Xiaolong Yin; Dejun Feng; Jungyeol Park; Junwook Hur; Yang Gao (Aquaculture, 2024)

Temperature and Dissolved Oxygen Lead to Behavior and Respiration Changes in Juvenile Largemouth Bass (Micropterus salmoides) during Transport - Fukun Gui; Haofeng Sun; Xiaoyu Qu; Shuai Niu; Guangyang Zhang; Dejun Feng (Fishes, 2023)
The study aimed to investigate the effects of temperature and dissolved oxygen on juvenile largemouth bass during transportation. The experiment involved four temperature groups: 20, 15, 10, and 5 °C. We analyzed the effects of acute and uniform cooling on fish behavior to determine the optimal approach for cooling. Then, we simulated transport under different temperature conditions while measuring the dissolved oxygen level and metabolic rate until all the fish died. The results showed that acute cooling significantly influenced the tail-beat frequency of fish compared with uniform cooling, while abnormal behaviors such as increased swimming, attempted jumping out of the water, and loss of balance were observed. As the transport temperature reduced, the oxygen consumption rate of fish significantly changed at 10 °C, being 2.6 times lower than at 15 °C, with values of 0.10 ± 0.02 and 0.47 ± 0.07 mg·g−1·h−1, respectively. The critical oxygen threshold (Pcrit) of fish were 1.90 ± 0.12, 1.61 ± 0.04, 1.15 ± 0.09, and 1.12 ± 0.25 mg·L−1 at 5, 10, 15, and 20 °C. In addition, below Pcrit, hypoxia-led behavior changes and oxygen consumption rate reduction were observed at every transport temperature. The findings suggest that the optimal low temperature can reduce metabolism and improve the hypoxia tolerance of juvenile largemouth bass. We recommend transporting largemouth bass at an optimal low temperature (15 °C), monitoring fish behavior, and maintaining oxygen levels above Pcrit during transport to prevent stress.

Slice-to-slice context transfer and uncertain region calibration network for shadow detection in remote sensing imagery - Hongyu Chen; Dejun Feng; Shaohan Cao; Wanqi Xu; Yakun Xie; Jun Zhu; Heng Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Study on the Corrosion Behavior of D36 Steel Plate and H62 Copper Alloy Net for Marine Aquaculture Facilities in Simulated Seawater - Fengfeng Gao; Fukun Gui; Dejun Feng; Xiaoyu Qu; Fuxiang Hu; Xu Yang (Journal of Marine Science and Engineering, 2023)
Marine aquaculture facilities have been working in a high salt and humidity marine environment for a long time, which makes them be inevitably affected by seawater corrosion, especially the main structures such as metal mesh and frame. Therefore, studying the corrosion behavior of net and frame steel is of great significance for the selection of materials and corrosion protection of marine aquaculture facilities. The influence of NaCl concentrations and immersion state on self-corrosion behavior and the influence of layer thickness and overlapping area on galvanic corrosion behavior of H62 copper alloy mesh/D36 steel plate was discussed in this study using weight loss and electrochemical measurements. The tensile tests were conducted to observe the influence of different corrosion conditions on maximum force and tensile strength of the net. The corrosion rate of the two materials increased rapidly with the increase of NaCl concentrations; the corrosion rate of both materials showed the decreasing trend with the extension of time, and the corrosion rate of H62 was always lower than D36 steel. When two materials were coupled, the galvanic corrosion rate would decrease with the increase of the layer thickness and overlapping area. The tensile results were consistent with the corrosion results. When these two materials work together, adding layer thickness or increasing the overlapping area is one of the ways to protect the frame steel to a certain extent.

Effect of inlet pipe design on self-cleaning ability of a circular tank in RAS - Yuji Zhang; Xu Yang; Jiajun Hu; Xiaoyu Qu; Dejun Feng; Fukun Gui; Fang Zhu (Frontiers in Marine Science, 2023)
To improve the water reuse efficiency of circular recirculating aquaculture tanks in Recirculating Aquaculture Systems (RAS) this research investigated the effect of inlet pipe deployment distance d (the distance between the stream tube hole and the tank wall) and the inlet pipe deployment angle α (the acute angle between the inlet pipe jetting direction and the nearest tank wall) on the self-cleaning ability of the circular aquaculture tank under dual and single inlet pipe designs. First, waste collection experiments were conducted to figure out the preferable inlet pipe design based on the efficiency of waste collection. Then, flow field measurement experiments were carried out employing the Particle Image Velocimetry (PIV) technique to measure the flow field in the near bottom layer of the tank, and the essential mechanism of the inlet pipe deployment on the waste collection was explored by analyzing the flow field and the corresponding hydrodynamic characteristic indicators, such as the average flow velocity ( v avg ), the uniformity coefficient of water flow (DU50), and the water resistance coefficient (Ct). The results indicate that the variations of waste movement, flow filed and hydrodynamic indicators are consistent in both designs of dual inlet and single inlet, and merely differ in the absolute value. Based on the comprehensive analysis, the optimal performance of self-cleaning can be obtained at α =0°~10°, 20°~30°, 40°~50° for d=1/2 r , 1/4 r , and 1/50 r , respectively. At the same flow rate condition, the jetting velocity of the inlet pipe in the single inlet pipe design is significantly greater than that in the dual inlet pipe design, and the hydrodynamic characteristics of the waste collection are better. Therefore, in circulating water aquaculture production, it is recommended to design the inlet pipe in a similar aquaculture tank to the single inlet pipe with d=1/4 r , α =20°~30°, thus improving the self-cleaning ability of the aquaculture tank. The study results also provide a reference for adjusting the inlet pipe in circular recirculating aquaculture tank.

Investigation of the inlet layout effect on the solid waste removal in an octagonal aquaculture tank - Jiajun Hu; Hanwen Zhang; Lianhui Wu; Fang Zhu; Xuefen Zhang; Fukun Gui; Xiaoyu Qu; Dejun Feng (Frontiers in Marine Science, 2022)
The optimization of the inlet layout in aquaculture systems is essential to ensure minimal solid waste discharge into the environment and improve fish production efficiency. In the present study, laboratory experiments were carried out to investigate the effects of the jetting position d / a (where d is the distance from the pipe axis to the tank side and a is the side length of the tank wall) and the jetting angle θ (the acute angle between the jetting direction and the nearest tank wall) on the solid waste removal efficiency in single-inlet and dual-inlet octagonal Recirculating Aquaculture System (RAS) tanks. To this end, three jetting positions ( d / a ) of 1/50, 1/8, and 1/4 and ten jetting angles ( θ ) of 0° to 80° were considered in the experiments. The Particle Image Velocimetry (PIV) technique was applied to measure the flow characteristics in the tank and analyze the solid waste removal under different working conditions. Residual mass of the solid waste, time of complete removal of solid waste, average velocity ( v avg ), and uniformity coefficient of velocity distribution ( DU 50 ) were analyzed to evaluate the solid waste removal efficiency. The obtained results indicate that adjustments of the inlet layout significantly affect the solid waste removal efficiency. It was found that a single-inlet tank with a d / a of 1/8 and θ in the range 10° to 40° has a good solid wastes removal performance, and the optimal efficiency occurs at a jetting angle of 30°. Moreover, the optimal solid waste removal efficiency in a dual-inlet tank can be achieved with a d / a ratio of 1/8 and a θ of 20°. The performed analyses reveal that from the aspect of solid waste removal efficiency, a tank with a d / a ratio of 1/8 outperforms a tank with a d / a ratio of 1/4 or 1/50. The results of this article offer novel insights in the layout of octagonal RAS tanks and provide a guideline to improve self-cleaning features of aquaculture tanks.

Dynamic Behavior of the Net of a Pile–Net-Gapped Enclosure Aquaculture Facility - Shun Wang; Dejun Feng; Fukun Gui; Zhijing Xu (Journal of Marine Science and Engineering, 2022)
A pile–net enclosure aquaculture facility, deployed in inshore waters, is a sustainable and ecological aquaculture pattern for rearing fish and other aquatic animals of economic value in China. It is essential to study the maximum force on and deformation of the net system of a pile–net enclosure facility to prevent its failure, since successful aquaculture is highly dependent on the longevity of the net system. In this study, a pile-net enclosure aquaculture facility with a gapped pile-net configuration was numerically investigated based on the lumped mass model. A Newton’s second-law-based motion equation was solved using Euler’s method. Finally, MATLAB was used to visualize the results. The results highlight that the force of a net system significantly increases with ocean loads, and the load of the entire net is mainly from the top half of the net. Moreover, the maximum force of the vertical rope occurs at the connection of the top channel steel. The maximum force of the horizontal rope and net twine occur in the rope near the still-water level and at the connection of the top channel steel, respectively. Thus, the net at those positions should be reinforced to prevent its failure.

Netting Damage Detection for Marine Aquaculture Facilities Based on Improved Mask R-CNN - Ziliang Zhang; Fukun Gui; Xiaoyu Qu; Dejun Feng (Journal of Marine Science and Engineering, 2022)
Netting damage limits the safe development of marine aquaculture. In order to identify and locate damaged netting accurately, we propose a detection method using an improved Mask R-CNN. We create an image dataset of different kinds of damage from a mix of conditions and enhance it by data augmentation. We then introduce the Recursive Feature Pyramid (RFP) and Deformable Convolution Network (DCN) structures into the learning framework to optimize the basic backbone for a marine environment and build a feature map with both high-level semantic and low-level localization information of the network. This modification solves the problem of poor detection performance in damaged nets with small and irregular damage. Experimental results show that these changes improve the average precision of the model significantly, to 94.48%, which is 7.86% higher than the original method. The enhanced model performs rapidly, with a missing rate of about 7.12% and a detection period of 4.74 frames per second. Compared with traditional image processing methods, the proposed netting damage detection model is robust and better balances detection precision and speed. Our method provides an effective solution for detecting netting damage in marine aquaculture environments.

Dynamic Response Analysis of Anchor Piles for Marine Aquaculture under Cyclic Loading - Jianqiao Kong; Tianyuan Zhang; Fukun Gui; Xiaoyu Qu; Dejun Feng (Journal of Marine Science and Engineering, 2022)
The anchor pile is widely used in marine aquaculture, and its uplift resistance capacity determines the safety performance of the marine aquaculture structure. Cyclic loads such as wind, waves, and currents in the marine environment affect the uplift resistance capacity of anchor piles. By carrying out a cyclic loading model test of anchor piles for marine aquaculture, the influence of loading amplitude, initial tension angle, and other factors on the uplift resistance of anchor piles was investigated. The experimental results showed that with an increase in the loading amplitude, the cumulative displacement and elastic displacement of the anchor pile under vertical and oblique loading increase, and the stiffness of the soil around the anchor piles decreases. The stability of the anchor piles is reduced. When the loading amplitude is the same, with the increase in the initial loading angle, the lateral cumulative displacement of the anchor pile increases. Meanwhile, the vertical cumulative displacement decreases, the stiffness of the soil around the anchor pile decreases, and the stability decreases.

Wheat-root associated prokaryotic community: interplay between plant selection and location - Yuyin Zheng; Zhihan Feng; Jialong Wang; Xiaoman Huang; Li Lei; Xue Zhang; Huili Cao; Dandan Fan; Minjie Yao; Dejun Han; Xiangzhen Li (Plant and Soil, 2021)

Isolation, primary culture, and morphological characterization of gland epithelium from forest musk deer (Moschus berezovskii) - Min Chen; Hang Jie; Zhongxian Xu; Tianyuan Ma; Meiyan Lei; Dejun Zeng; Guijun Zhao; Xiaolan Feng; Chengli Zheng; Chenglu Zhang; Zhengjie Liang; Diyan Li (In Vitro Cellular & Developmental Biology - Animal, 2018)

Development, characterization, genetic diversity and cross-species/genera transferability of ILP markers in rubber tree (Hevea brasiliensis) - Dejun Li; Zhihui Xia; Zhi Deng; Xianghong Liu; Fuying Feng (Genes & Genomics, 2013)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

Expression Profiles of 10,422 Genes at Early Stage of Low Nitrogen Stress in Rice Assayed using a cDNA Microarray - Xingming Lian; Shiping Wang; Jianwei Zhang; Qi Feng; Lida Zhang; Danlin Fan; Xianghua Li; Dejun Yuan; Bin Han; Qifa Zhang (Plant Molecular Biology, 2006)